Characterization of an immunoglobin cDNA clone containing the variable and constant regions for the MOPC 21 kappa light chain. - Strathearn, M D (1978)
Nucleotide sequence analysis and restriction endonuclease mapping have been used to characterize a cDNA copy of immunoglobulin MOPC 21 Kappa mRNA clones in the bacterial plasmid pMB9. Three regions of the inserted cDNA of plasmid pL21-1 have been sequenced and match the known protein sequence at amino acid residues 1-24, 128-138 and 171-179. With these sequences to provide absolute correlations between the restriction map and the structural gene sequence it has been possible to exactly deduce the positions of all 11 of the insert restriction sites mapped within the structural gene. The pL21-1 insert contains the complete variable and constant regions as well as parts of the 3' untranslated and polypeptide leader coding sequences.